Experimental and numerical comparison q-switched fiber laser generation using graphene as saturable absorber - Awang, Noor Azura; Aziz, Nor Syuhada; Azmi, Atiqah Nabieha; Hadi, Fatin Shaqira; Zakaria, Zahariah (2018)
We demonstrated the comparison experimentally and numerically a compact Q-switched erbium-doped fiber (EDF) laser based on graphene as a saturable absorber (SA). By optically driven deposition of graphene on a fiber core, the SA is constructed and inserted into a diode-pumped EDF laser cavity. Lasing in CW region starts at 10 mW, whereas stable self-starting Q-switching with a central wavelength of 1530 nm begins at 18 mW. In this paper, at 35 mW, the maximum pulse energy reaches at 2 µJ with pulse repetition rate of 1 MHz and the narrowest pulse width is around 10 µs is obtained. The stability of the pulse is verified from the radio-frequency (RF) spectrum with a measured signal-to-noise ratio (SNR) of 48 dB. In this study, the design is compared with the simulation using the Optisystem software. The output power of the experimental study is also compared with the simulation to examine the performance.